Hypnotherapy to Promote Weight Loss at First Trimester on Pregnant Women with Emesis Gravidarum at Muhammadiyah Gresik Hospital - Siti Hamidah; Siti Mudlikah (Journal for Quality in Public Health, 2020)
Background: The nutritional status of pregnant mothers affects the growth and development of fetus in the womb. The effort of hypnotherapy with the method of unconscious mind makes the condition relaxed, calm, focus decreases stress and affects the weight of early pregnant women. Purpose: The purpose of the study was to identify hypnotherapy interventions in young expectant mothers (first trimester) with emetic gravidarum on maternal weight gain. Methods: This research is a type of experimental quasi, with time series design in September 2019-April 2020. The research population is all of the first tirmester pregnant mothers at Muhammadiyah Gresik Hospital. Number of samples selected 100 respondents with quota sampling. Data collection with KIA books on first, second and third visit. Data analysis with normality test and ANOVA test. Results: The results showed a result of p < 0.001, meaning that H0 was rejected, i.e. there is an average difference in weight increase in the three groups of measurement time intervals (p < 0.05). The caller's conclusion is a hypnotherapy influence with the weight gain of pregnant women. Conclusion: Hypnotherapy can affect mothers on a psychic basis about the importance of eating while pregnant for the health of mothers and babies that are conceived.